Lived experiences of social support in Paralympic swimmers: A protocol for a qualitative study - Paul Martin; Alison Rushton; Nicola R Heneghan; Andrew Soundy; Beth Aitchison (BMJ Open)
Introduction Over the past decade, there has been an increase in awareness of and investment into disability sport as a result of the ‘Paralympic Movement’. The provision of personal and professional support to elite athletes is important for the well-being and success of the athlete, with various studies advocating a holistic approach to performance enhancement. However, little is known about social support experiences in elite para-swimming. Swimming is a popular Paralympic sport and the British para swimmers have been very successful in recent years, most recently winning 47 medals at Rio 2016. This study will be the first to explore the lived experiences of British Paralympic swimmers with respect to the personal and professional support available, perceived use of the support network and the influence it has on well-being and performance.Methods and analysis A hermeneutic phenomenological study will be undertaken using a subtle-realist paradigmatic view. A purposive sample of British Paralympic swimmers will be recruited to enable exploration of social support experiences. In-depth semistructured interviews will explore participants’ experiences of being an elite para-athlete, their support network, the social support available and how they perceive it relates to their well-being and performance. Strategies including reflexivity and member checking will be used to ensure trustworthiness. Data will be analysed following the Framework Method; a seven-stage process used for qualitative data analysis.Ethics and dissemination This study has ethical approval (ERN_20–0344) granted by the University of Birmingham in April 2020. The findings of this study will be published in a peer-reviewed journal and disseminated to key stakeholders in elite para-sport to inform support services and improve athlete well-being and performance.